Religiosity and Time Displacement: An Examination of the Effect of Social Media and Education Background on Islamic University Students’ Religiosity - Akbar Jihad Ibnu Arif Sagran; Tengku Siti Aisha Tengku Mohd Azzman Shariffadeen (Kalijaga Journal of Communication, 2023)
This study explores the influence of increased social media activity on changes in conventional communication and time allocation. The excessive use of social media and its susceptibility to changes in religiosity are examined. At International Islamic University Malaysia (IIUM), students actively utilize social media as a means of communication and information gathering. This research aims to examine how social media usage duration and educational background among students contribute to the enhancement of religiosity. The research hypothesis is supported through statistical analysis in a quantitative approach, employing a cross-sectional online survey involving 321 IIUM students. The findings indicate a positive correlation between social media usage and Islamic religiosity among IIUM students. Consequently, these students are more inclined to access positive rather than negative content on social media. Significantly, the study found that IIUM students have a higher Islamic religiosity. The impact of social media usage among IIUM students is predominantly positive rather than negative. Furthermore, the research paper addresses the discussions and limitations and provides suggestions for further research.